EFFICACY AND ADAPTATION OF E-LEARNING IN INDIAN HIGHER EDUCATION INSTITUTIONS DURING COVID-19 - Jayashree Saha; Papori Baruah (Інформаційні технології і засоби навчання)
The unpredictable lockdown period due to COVID-19 has kept everything on hold, and along with other sectors, the educational sector is the most affected. This study attempted to map out the fragility of higher educational institutions in adopting new learning methods and the effectiveness achieved. This is descriptive research based on an empirical investigation of the current issues related to sudden changes in the knowledge delivery process in regular classes of colleges and universities in developing countries like India. Five constructs, namely quality delivery, effectiveness, organisational support, self-efficacy, and readiness were evaluated to measure learners’ perceived satisfaction. Appropriate statistical tools were applied to analyse the data, along with hypothesis testing. A few institutions have effectively adjusted the learning process, but its prolificacy is doubtful in the majority of cases. Many (about 62 percent) reported that through assignments and study materials, it is difficult to clear the concepts, especially in the case of practical subjects. There is an opinion that e-learning appears not to be as fruitful as regular conventional classes. It has become a little difficult to transform the centuries-old classroom teaching model due to a paucity of infrastructural readiness, prior experience in e-learning, drawbacks in learning methods, etc., which needs to be addressed by administration. The main barriers, as per our study, are the paucity of interactivity between the parties and drawbacks in the method adopted for teaching. This research did not include premier institutions like IITs, AIIMS, and other highly rated institutes in India, as our goal was to articulate the real situation below the creamy layer. The COVID-19 pandemic has opened new avenues to eliminate drawbacks and reconsider the pedagogical methods, teacher training, examination system, etc. for the insertion of e-learning in the education system.